Studi Etnobotani Tumbuhan Obat Pada Masyarakat Suku Kaili Rai di Desa Toga Kecamatan Ampibabo Kabupaten Parigi Moutong Sulawesi Tengah - Neneng Sukmawati; Eny Yuniati; Ramadanil pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2013)
Research on medicinal plants in the study of ethnobotanyKailiRai tribe in Toga village has been conducted from November to February 2013 in Toga village, AmpibaboSubdistrict, MoutongParigi District, Central Sulawesi. This study was aimed to obtain information about the types of plants used as traditional medicine, plant organs used, types of habitus is used, the type of disease that can be treated and how to use of medicinal plants This research used exploratory survey methods and methods of Participatory Rural Appraisal. Based on the survey results revealed that as many as 46 species of plants and herbs used as medicine are most widely used are as many as 7 species of Zingiberaceae family. Habitus herbs used include trees, shrubs and herbs. habitus of the most widely used as a medicinal plant is herbaceous by 50%. Parts of the plant are used, among other roots, rhizomes, bark, leaves, and fruits. Part of the organ that is most widely used leaves by 47,36%. Toga villagers utilized drugs to treat diseases such as gout, high blood pressure and burns. Medicinal plants used by boiled, mashed, squeezed and baked before serving. Keywords : Ethnobothany, Medicinal plants, Toga Village.